Linkage mapping, molecular cloning and functional analysis of soybean gene Fg3 encoding flavonol 3-O-glucoside/galactoside (1 → 2) glucosyltransferase - Di, Shaokang (BMC Plant Biol, 2015)
BACKGROUND: Flavonol glycosides (FGs) are major components of soybean leaves and there are substantial differences in FG composition among genotypes. The first objective of this study was to identify genes responsible for FG biosynthesis and to locate them in the soybean genome. The second objective was to clone the candidate genes and to verify their function. Recombinant inbred lines (RILs) were developed from a cross between cultivars Nezumisaya and Harosoy. RESULTS: HPLC comparison with authentic samples suggested that FGs having glucose at the 2″-position of glucose or galactose that is bound to the 3-position of kaempferol were present in Nezumisaya, whereas FGs of Harosoy were devoid of 2″-glucose. Conversely, FGs having glucose at the 6″-position of glucose or galactose that is bound to the 3-position of kaempferol were present in Harosoy, whereas these FGs were absent in Nezumisaya. Genetic analysis suggested that two genes control the pattern of attachment of these sugar moieties in FGs. One of the genes may be responsible for attachment of glucose to the 2″-position, probably encoding for a flavonol 3-O-glucoside/galactoside (1 → 2) glucosyltransferase. Nezumisaya may have a dominant whereas Harosoy may have a recessive allele of the gene. Based on SSR analysis, linkage mapping and genome database survey, we cloned a candidate gene designated as GmF3G2″Gt in the molecular linkage group C2 (chromosome 6). The open reading frame of GmF3G2″Gt is 1380 bp long encoding 459 amino acids with four amino acid substitutions among the cultivars. The GmF3G2″Gt recombinant protein converted kaempferol 3-O-glucoside to kaempferol 3-O-sophoroside. GmF3G2″Gt of Nezumisaya showed a broad activity for kaempferol/quercetin 3-O-glucoside/galactoside derivatives but it did not glucosylate kaempferol 3-O-rhamnosyl-(1 → 4)-[rhamnosyl-(1 → 6)-glucoside] and 3-O-rhamnosyl-(1 → 4)-[glucosyl-(1 → 6)-glucoside]. CONCLUSION: GmF3G2″Gt encodes a flavonol 3-O-glucoside/galactoside (1 → 2) glucosyltransferase and corresponds to the Fg3 gene. GmF3G2″Gt was designated as UGT79B30 by the UGT Nomenclature Committee. Based on substrate specificity of GmF3G2″Gt, 2″-glucosylation of flavonol 3-O-glycoside may be irreconcilable with 4″-glycosylation in soybean leaves. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-015-0504-7) contains supplementary material, which is available to authorized users.